2023
DOI: 10.1021/acs.chemmater.2c03811
|View full text |Cite
|
Sign up to set email alerts
|

Design of Dithienopyran-Based Conjugated Polymers for High-Performance Electrochromic Devices

Abstract: Numerous conjugated polymer-based electrochromic devices (ECDs) have been developed, but the correlation between electronic properties of electrochromic polymers (ECPs) and their EC performance, especially response speeds, has been rarely explored. In this work, we propose two new dithienopyran-based ECPs containing different heteroatoms with distinct electronic characteristics to elucidate the effect of the electronic structure of ECPs on EC performance. When electron-donating alkoxy groups are fused into ECP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…To further investigate the color change of the films, the optical variation was also tracked in terms of the CIE L*a*b* 1976 Color Space, as shown in Figure g,h. L* represents the transmittance of light through a sample, while a* represents how red versus green the material is, and b* represents how red versus yellow the material is. , From the experimental results, the optical colors of the two conjugated polymers were quite similar. For example, in their neutral state, both polymers showed transparent (e.g., ( L* , a* , b* ) values of (98.8, −2.3, 5.0) and (97.4, 0.2, 4.6) for pCBCB and p3CBCB, respectively).…”
Section: Resultsmentioning
confidence: 91%
“…To further investigate the color change of the films, the optical variation was also tracked in terms of the CIE L*a*b* 1976 Color Space, as shown in Figure g,h. L* represents the transmittance of light through a sample, while a* represents how red versus green the material is, and b* represents how red versus yellow the material is. , From the experimental results, the optical colors of the two conjugated polymers were quite similar. For example, in their neutral state, both polymers showed transparent (e.g., ( L* , a* , b* ) values of (98.8, −2.3, 5.0) and (97.4, 0.2, 4.6) for pCBCB and p3CBCB, respectively).…”
Section: Resultsmentioning
confidence: 91%
“…The total chamber volume was approximately 50 in. 3 (820 cm 3 ). The top of the chamber has a standard conflating door for sample exchange.…”
Section: Film Fabrication and Characterization 211 Solutionmentioning
confidence: 99%
“…However, inorganic EC materials are limited in manifesting diverse colors and coloring adjustments. Organic materials such as conducting polymers and viologens have recently become an intensive research topic. The conducting polymers have several advantages over inorganic compounds as EC materials, including good electrochemical stability, fast switching speed, high coloring efficiency (CE), easy large-area processing, and color tuning through chemical modification. Also, triphenylamine (TPA)-containing polymers have been developed as an attractive family of EC materials because of their colorless neutral state and intriguing EC behaviors. In recent years, redox-active materials with optical absorption change in the near IR (NIR) region have drawn significant attention due to their potential applications in optical communication, data storage, and thermal control in buildings and spacecraft. , For example, Wan et al reported that the quinone-containing EC materials revealed high absorption in NIR upon electrochemical reduction .…”
Section: Introductionmentioning
confidence: 99%